The influence of using computers to remedy learner errors and misconceptions in functions at grade 11 - Mugwagwa, Tsitsi Mable (My University, 2017)
The aim of the study was to investigate what influence the use of ICT teaching and learning such as Geogebra software and you tube videos had on grade 11 South African learners’ understanding of functions. The theoretical underpinnings informing this study were constructivism, socio-cultural learning theories, variation theory and the Technological Pedagogic Content Knowledge. A mixed method approach was employed using a Quasi-experiment design. Two grade 11 classes from a South African township school in Soweto were used in the study; one as the control group and the other as the experimental group. These samples were purposefully and conveniently selected for the study. The researcher administered a pre-test to both groups followed by a teaching intervention where the control group was taught using traditional methods while the experimental group was taught using computers. Semi structured interviews were conducted to establish reasons for learner errors and misconceptions after marking the pretest while a semi structured interview guided by specific questions was used to establish the effects using computers with the experimental group after the posttest. After the intervention, a posttest was administered to both groups. Data was analyzed from the test scripts for all the learners to establish the misconceptions that learners in this study have on functions and later on from the test scripts of learners separately in their respective groups to establish the influence of using ICT in the intervention. Interviews on the errors identified from the pretest were conducted from a sample of learners from either group to explain the reason for their errors while at a later stage, learners interviewed were selected from the experimental group to give insight into the influence of using computers. Data was analyzed qualitatively and quantitatively. The results indicated that the using learner errors and misconceptions as a resource for intervention had positive impact on learner performance for both groups. However, there was better improvement from those learners who used computers in their intervention than those students who used traditional methods. The use of computers in the mathematics classroom yielded a positive attitude towards mathematics. With an improved attitude, there was also an improvement in the learner performance, hence proving that using computers yields better results.It is also hoped that the study will inform policy developers in mathematics education on how technology can be incorporated into mathematics classrooms to enhance learning.
A research report Submitted in partial fulfilment of the requirements for the degree of Masters of Science to Faculty of Science, University of the Witwatersrand, Johannesburg March 2017.
Keywords: Educational technology; Education--Effect of technological innovations on--South Africa